Capillary Gas Chromatographic Determination of Isoniazid in Pharmaceutical Preparation by Pre-column Derivatization with Acetylacetone - Khuhawar, M.Y.; Zardari, L.A.; Laghari, A.J. (Asian Journal of Chemistry, 2010)
Antituberculosis drug isoniazid and toxic substance hydrazine have been determined by capillary column gas chromatography after precolumn derivatization with acetylacetone. Phenyl hydrazine when present together with isoniazid and hydrazine also separated completely from the column HP-5 (30 m × 0.32 mm I.D) connected with flame ionization detection. Phenyl hydrazine was used as an internal standard. The elution was carried out at initial column temperature 120 ºC with heating rate 50 ºC/min up to 280 ºC, with nitrogen flow rate of 1.5 mL/min and split ratio was 20:1. The linear calibration range for isoniazid was observed 6.2-100 μg/mL with detection limit of 3.1 μg/mL corresponding to 150 pg reaching to the detector. Similarly, the linear calibration range for hydrazine was 7.1-57 μg/mL with detection limits of 2.3 μg/mL. The method was applied for the determination of isoniazid and hydrazine from pharmaceutical preparations and relative deviation of isoniazid from labelled values was within 1.0 to 1.4 %. The amount of recovery of isoniazid from pharmaceutical preparations was 97 % with RSD 3 %.